(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The study applied the ANN (12, 12, 1) model in order to analyze hypertension cases for Gweru Provincial Hospital. The data used in the study cover the period January 2010 to December 2019 while the out-of-sample period is January 2020 to December 2021. The applied model is quite stable and acceptable as shown by its minimum forecast evaluation statistics (i.e Error, MSE, MAE) as well as residuals which are as close to 0 as possible. The results of the study basically indicate that hypertension cases at GPH will slightly decline over the January 2020 to December 2021. The study recommends the following: [i] GPH ought to reduce bottlenecks in the management of hypertension; [ii] GPH should make sure essential medicines for treatment of hypertension are always in place; [iii] GPH should promote a healthy diet during its community-based health campaigns.